Erysipelas and lymphangitis in patients undergoing lymphedema treatment after breast-cancer therapy - Pereira de Godoy, José Maria (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
Aim: The aim of this study was to evaluate the prevalence of erysipelas and lymphangitis in a group of patients under treatment for lymphedema after breast-cancer therapy. Methods: A random observational prospective study of the incidences of lymphangitis and erysipelas was performed for 66 patients with arm lymphedema after breast-cancer treatment. The study was carried out between March 2006 and December 2007 at the Godoy Clinic in Sao José do Rio Preto, Brazil. The clinical evaluation of the participants was performed weekly before the start of treatment, with patients being required to immediately report any complications to the attending service. Results: The mean time of follow-up of the patients between their treatment for breast cancer and the start of this study was 12.3 months, and three complications (4.5%) occurred; two cases of lymphangitis were reported after insect bites and one case of erysipelas after a hand injury, with repeat episodes reported by all three patients. Conclusion: In spite of prophylactic advice regarding lymphangitis and erysipelas during treatment for lymphedema after breast-cancer therapy, patients are subject to complications; however, this initself does not justify the use of prophylactic antibiotic therapy.
Keywords: breast; Breast Neoplasms; Dojka, novotvorbe; dojke; Erizipel; Erysipelas; Limfangitis; Limfatični edem; limfedem; Lymphangitis; Lymphedema; Prospective Studies; Prospektivne študije; rak (medicina); Therapy; zapleti; zdravljenje